PERTANGGUNGJAWABAN PIDANA KORPORASI MASKAPAI PENERBANGAN SIPIL DALAM UU NO 1 TAHUN 2009 TENTANG PENERBANGAN - AGUS FRENGKI BANJARNAHOR; SADDAM HUSEIN HASIBUAN; KRISTOFEL ABLIO MANALU; SILWANUS MANAO; MUHAMMAD SIDIQ (LP2MTBM MAKARIOZ, 2020)
This research discusses how the legal protection measures for air transport passengers under Law No. 1 of 2009 onaviation, how to Answer corporate criminal liability of civil aviation in LAW No. 1 year 2009 on flight. In the discussion usingthe normative legal research method of reviewing law number 1 year 2009 and Law number 40 year 2007 aboutcorporations. The results of this thesis are related to the legal protection of the passengers is about the determination of theresponsibility of air transportation companies to passengers, indemnity, and remedies for passengers who suffer losses.Transportation of commercial air both international and national flights is concerned with the responsibility of the need for theremoval of losses suffered by the users of air transportation services, namely passengers, baggage owners, shippers orcargo recipients and also losses incurred by third parties. Possible losses that may be experienced by users of airtransportation services include: death or deform or injuries, loss, destruction, damage to goods, as well as flight delays.